Spray nas mãos, afetos nos muros: cartografia de inter(in)venções do graffiti no cotidiano de jovens inventores. - Lavor Filho, Tadeu Lucas de (2020)
The present master's research brings as an investigation field the articulation between educational and school territories, graffiti and modes of subjectivation through an intervention-research with cartography method on the outskirts of the city of Fortaleza. Graffiti productions are located within the scope of the research on the school walls, in the streets, in the squares, in the institutions, among other registration spaces. Graffiti is generally understood as the production of arts with an aesthetic structure of risks, symbols, images, letters, especially the spontaneous expression that wants to register the context, the situation, the scene, the real and the thinkable that it usually has. as support for walls and walls. Such productions are appropriated by young people and start to be engendered in the school culture in which both signal records of liberties, desires and life stories. It is in this interstice that graffiti engenders modes of subjectivation that can tension the school routine. Therefore, in view of the foregoing, we designate a starting question: how have graffiti productions produced by / by young people been operationalized in educational practices inside and outside the school routine? We list as the general objective of this research to map the interventions and tensions that engender graffiti productions with young people engaged in educational practices inside and outside the school routine. The specific objectives were: a) to map how graffiti interventions are produced and experienced and their relationship with youth on the outskirts of Fortaleza; b) to analyze how young graffiti producers are subject to this practice; c) problematize graffiti interventions produced with and by young people in educational practices. The methodology anchored in this research is research-intervention with handling of cartography. The research field that makes up the cartographic map of this research is the outskirts of Fortaleza and a full-time public high school located in the territory that had an elective graffiti discipline offered. The theoretical-methodological devices operated were: participant observation and daily conversations, field diary, interviews under cartographic management, and a group with young students. The analysis of the research data consisted of the Discourse Analysis device in the Foucaultian perspective. In conclusion, the graffiti produced in the peripheries have been managed under collective and individual issues based on confronting issues such as racism, social inequality, the participation of women and the democratization of urban art in peripheral territories and these issues are lines of forces that mobilize and they are subjectivators of the trajectories of young graffiti artists and graffiti artists. Regarding educational practices, graffiti is experienced as an educational device to promote social transformation in the lives of young people living in the periphery with actions outside and inside school spaces. Finally, the elective discipline of graffiti proved to be a teaching experience in which the political component emptied due to the emphasis on teaching the technique and aesthetics of art. It is hoped that this research can contribute to studies in Psychology and other areas that focus on the processes of subjectivation and art phenomena in educational contexts.